Answer:
x = [tex]-\frac{2}{3}[/tex]
Step-by-step explanation:
I used the FOIL method
[(2x + 3) (3x + 2)] − [(3x + 2) (2x− 3)] = 0
[tex](6x^{2} +4x+9x+6) - (6x^{2} -9x+4x-6)=0[/tex]
[tex](6x^{2} +13x+6) - (6x^{2} -5x-6)=0[/tex]
[tex](6x^{2} +13x+6) - 6x^{2} +5x+6=0[/tex]
combine like terms
[tex]6x^{2} -6x^{2} = 0[/tex]
[tex]13x+5x=18x[/tex]
[tex]6+6=12[/tex]
so, [tex]18x +12 = 0[/tex]
subtract 12 on both sides
[tex]18x=-12[/tex]
divide by 18 to isolate x
[tex]x=-\frac{12}{18}[/tex]
and simplifies to
[tex]x=-\frac{2}{3}[/tex]